Análisis de la interfaz de usuario de los sitios web de las parroquias del cantón Latacunga 2023. - Caiza Paneluisa, Marlon David (2023)
The purpose of the present research was to analyze the websites of the rural parishes of Latacunga Canton using the TAW tool and content analysis in order to obtain results of usability, accessibility, user experience, etc. Due to the lack of maintenance of the sites, a problem has been created that prevents the correct functioning of the web. The objective of this project was based on the analysis of the web sites of the 9 rural parishes of the Latacunga canton and through the results obtained a prototype of a universal interface was designed, the design of the interface has a touristic and communication purpose. The development of the project included documentary research with which we obtained theoretical and technical knowledge about usability and interface design and bibliographic research which gathered information from the parishes about heritage assets that are part of the culture and history of each of the parishes, as well as their geographical situations. Research techniques such as survey, observation, interview, focus group, identified different manifestations in the usability test of the prototype. The prototype design was based on the user-centered design procedure proposed by Yusef Hassan; Francisco J. Martín Fernández and Ghzala Iazza, which proposes in stages the whole procedure of design, development, evaluation and implementation of the product focused on the needs, objectives and characteristics of the user. With the result obtained, the information gathered from the use of multimedia as graphic media, an accessible interface was designed, as well as easy access to provide the user with a digital media that generates a good experience when entering the parish website. Concluding that the established needs are solved with decisive ideas that are reflected in design projects with innovation.